The Impact Of Digital Promotion Development On Tourist Visitation Levels In Pandanrejo Village, Purworejo District, Indonesia - Linandar Tanuwijaya; Dendy Sundayana; I Gusti Agung Wahyu Adrian; Edwin Adriansyah; Mohamad Ridwan (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2025)
This study analyzes the impact of digital promotion development on tourist visitation rates in Pandanrejo Tourism Village, Purworejo Regency, by linking upstream indicators (digital activities and findings) to downstream indicators (verified visits). The empirical background shows a “surge–plateau–correction” pattern in visitation data: the annual total rose drastically from 1,661 (2020) to 8,067 (2021), remained relatively stable at 8,094 (2022), and then corrected to 4,672 (2023); monthly dynamics were prominent in March 2023 (1,766) and November 2023 (716), indicating a dependence on moments/events as the main driver. Conceptually, the study positions digital promotion (social media, SEO/local search, online reviews, UGC, and OTA channels) as a stimulus that works through the mediators of destination image, trust, and visit intention before it manifests into visits. . The proposed methodology is a mixed-methods explanatory sequential: (i) quantitative quasi-experimental through Interrupted Time Series (ITS) and multi-period Difference-in-Differences (DiD) (with similar comparison villages), as well as transfer function/ARIMAX to include digital indicators as leading indicators; (ii) PLS-SEM survey to test the image–trust–intention→visit mechanism path. Descriptive results indicate that the 2021–2022 increase is in line with the possible activation of digital promotions, while the 2023 correction suggests a weakening of upstream drivers and/or the influence of external factors (access, weather, event calendar). Practical implications include orchestrating a content calendar 6–8 weeks before the “anchor moment” (e.g., March/November), strengthening Google Business Profile (photos, FAQs, booking links), activating curated UGC, and measurement by design with upstream–downstream KPIs (reach/engagement/CTR/sentiment → tickets/parking, activity participation, homestay occupancy) and cost per visit. The study’s contribution lies in operationalizing a causal measurement framework in the context of tourism villages, which has been underrepresented. Key limitations, the lack of integration of digital-to-visit data and the absence of verified comparators are set as further agendas to ensure causal attribution, assess heterogeneity of impact across segments, and optimize promotional cost efficiency.